Pengaruh Motivasi Kerja, Lingkungan Kerja dan Kepuasan Kerja Terhadap Kinerja Pegawai Pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Mataram - Yeni Febrian; Zainal Abidin; Sri Wahyulina (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2023)
This research is entitled the influence of work motivation, work environment and job satisfaction on the performance of Mataram City BKPSDM office employees. Aims to determine the influence of work motivation, work environment and job satisfaction on employee performance. The type of research used is causal associative research with a quantitative approach. The data collection method used is the census method. The population and respondents in the research were 41 employees of the Mataram City BKPSDM office. The analytical tool used is Multiple Linear Regression using SPSS version 29. The results of the analysis show that: (1) work motivation has a positive and significant effect on employee performance (2) the work environment has a positive and significant effect on employee performance and (3) job satisfaction has an effect positive and not significant on employee performance.